Summer Distribution of Marine Birds in the Western Beaufort Sea - Fischer, Julian B.; Larned, William W. (ARCTIC, 2004)
Proposed expansion of oil and gas development into offshore waters of the Beaufort Sea has raised concerns that marine birds could be affected by disturbance and oil spills. We conducted aerial surveys to determine the composition and distribution of avian species in the western Beaufort Sea. We sampled marine waters up to 100 km from shore, between Cape Halkett and Brownlow Point in June, July, and August of 1999 and 2000 and between Point Barrow and Demarcation Point in July 2001. Approximately 90% of the birds we observed were sea ducks, predominantly long-tailed ducks (Clangula hyemalis), king eiders (Somateria spectabilis), and scoters (Melanitta spp.). Densities of most species decreased with distance from shore, although king eider densities were higher in deeper, offshore waters. Densities of long-tailed ducks increased in nearshore coastal lagoons at the onset of post-breeding moult, and densities of eiders increased offshore during their peak moult migration. In general, bird densities were highest in areas with less than 30% ice cover, although high densities of king eiders occurred in areas with 30%-60% ice cover. Our results suggest species-specific uses of the Beaufort Sea in summer for moulting, migration, brood rearing, and foraging. The vulnerability of marine birds to potential oil spills and disturbance will depend on the location of facilities, timing of events, and ice conditions. Un projet d'expansion de l'exploitation pétrolière et gazière dans les eaux du large de la mer de Beaufort a soulevé des questions au sujet des retombées éventuelles pour les oiseaux marins suite aux perturbations et à des déversements d'hydrocarbures. On a effectué des relevés aériens pour analyser la composition et la répartition des espèces aviaires dans la mer de Beaufort occidentale. On a échantillonné les eaux marines jusqu'à une distance de 100 km du rivage, en juin, juillet et août de 1999 et de 2000, entre Cape Halkett et Brownlow Point et, en juillet 2001, entre Point Barrow et Demarcation Point. ...